2017
DOI: 10.1108/jaee-08-2016-0072
|View full text |Cite
|
Sign up to set email alerts
|

The effects of board experience and independence on mitigating agency conflict

Abstract: Purpose The purpose of this paper is to investigate the impact of board experience and independence on mitigating agency conflict between shareholders and managers. Design/methodology/approach This paper uses a panel data of 137 firms listed on stock exchanges in Ghana and Nigeria over a period of seven years. System generalized method of moments and other estimation techniques were adopted for the study. Using agency and resource dependence theories, board experience and independence ignored in previous stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 110 publications
(107 reference statements)
1
16
0
1
Order By: Relevance
“…The finding of positive effect of DEduQ₁ is consistent with empirical outcome of Amore et al, 2019 andDarmadi, 2013. In accordance with the findings from baseline assessment, robustness test result also showed that the presence of directors with bachelor's degree in law (DEduQ₂) is negatively related to economic value of equity and statistically significant at 5 percent (i.e., coefficient: -5.0745; p-value<0.05) (see Liu and Sun, 2021). The robustness assessment also reveals the presence of negative association between cognitive experience (DCogExp) and economic value of equity as the proportion of directors with banking and finance expertise is significantly linked to impaired bank economic net worth (i.e., coefficient: -1.885; p-value<0.05) consistent with Agyemang & Appiah (2017). Finally, and contrary to the blanket notion that the composition of independent outside directors enhances firm financial performance, the robustness test re-affirmed the accuracy of baseline assessment which indicates, to a large extent, that the appointment and inclusion of non-executive directors are cognitive based, and that the presence of independent non-executives (CINED) may be a tokenism and potentially, though not significant, jeopardizes increased economic value of equity (i.e., coefficient: -0.0540; p-value>0.05).…”
Section: Robustness Testsupporting
confidence: 60%
See 1 more Smart Citation
“…The finding of positive effect of DEduQ₁ is consistent with empirical outcome of Amore et al, 2019 andDarmadi, 2013. In accordance with the findings from baseline assessment, robustness test result also showed that the presence of directors with bachelor's degree in law (DEduQ₂) is negatively related to economic value of equity and statistically significant at 5 percent (i.e., coefficient: -5.0745; p-value<0.05) (see Liu and Sun, 2021). The robustness assessment also reveals the presence of negative association between cognitive experience (DCogExp) and economic value of equity as the proportion of directors with banking and finance expertise is significantly linked to impaired bank economic net worth (i.e., coefficient: -1.885; p-value<0.05) consistent with Agyemang & Appiah (2017). Finally, and contrary to the blanket notion that the composition of independent outside directors enhances firm financial performance, the robustness test re-affirmed the accuracy of baseline assessment which indicates, to a large extent, that the appointment and inclusion of non-executive directors are cognitive based, and that the presence of independent non-executives (CINED) may be a tokenism and potentially, though not significant, jeopardizes increased economic value of equity (i.e., coefficient: -0.0540; p-value>0.05).…”
Section: Robustness Testsupporting
confidence: 60%
“…The presumption has been that, having corporate boards comprised of directors of different races and gender and those with diverse cognitive skills, would provoke board vigilance, due diligence, and mobilization of vital resources that support the corporate common good (Nuber & Velte, 2021;Kroll et al, 2008). Interestingly, prior comparable studies with combined theoretical framework have reported fascinating evidence linking certain elements of board demographic and cognitive diversity to corporate task and financial performance (Amorelli & Garcí a-Sá nchez, 2020;Rubino et al, 2017;Agyemang & Appiah, 2017;Kiel & Nicholson, 2003;Hillman & Dalziel, 2003).…”
Section: Literature Review Research Framework and Hypothesis Developmentmentioning
confidence: 99%
“…Following these studies (Assenga et al, 2018;Badu and Appiah, 2017;Maswadi and Amran, 2023;Oliveira et al, 2022;Poletti-Hughes and Mart ınez Garcia, 2022;Pugliese et al, 2014;Wongsinhirun et al, 2023), we employ the agency theory and resource dependence theory to establish the association between board diversity and systematic risk. The integration of agency and resource dependency theories allows for a richer understanding of the relationship of board capital to monitoring and resource provision (Hillman and Dalziel, 2003).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Resource dependency theory strongly advocates that attributes such as expertise, experience and skills are necessary for the board to be effective (Badu and Appiah, 2017).…”
Section: Board-specific Skills Diversity and Systematic Riskmentioning
confidence: 99%
“…As a result, the principal has to spend more expenses to ensure that all agents' decisions do not harm them. Corporate governance is believed to reduce agency conflict by providing board experience and board independence, which is crucial in providing monitoring information (Badu & Appiah, 2017). A high level of corporate governance that a large board can indicate and an effective audit committee significantly impacts reducing the agency cost (Allam, 2018).…”
Section: Corporate Governance and Environmental Performancementioning
confidence: 99%